THE IMPACT OF PROMOTION, PRICE, AND SERVICE QUALITY ON PURCHASING DECISIONS: AN INVESTIGATION OF SAE CAR AUDIO IN GEMOLONG CITY - Seputri Mahayu Bhirdhanata; Rini Handayani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research examines the impact of promotion, price, and service quality on purchasing decisions in a case study conducted at SAE Audio in Gemolong City, Central Java. The study involved 85 respondents selected through the Non-Probability Sampling method. Data analysis encompassed several statistical techniques, including the instrument test (validity & reliability), classical assumption test (normality, multicollinearity and heteroscedasticity, and autocorrelation), multiple linear regression analysis (determination analysis, model feasibility test, and hypothesis test). The findings of this study reveal that promotion, price and service quality each have an positively and significantly impact on purchasing decisions. Keywords: Purchase Decision, Promotion, Price, Service Quality